2018
DOI: 10.1002/chem.201800306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azo Dyes from Mesoionic Carbenes and Nitrous Oxide

Abstract: Covalent adducts of imidazole-based mesoionic carbenes and nitrous oxide (N O, "laughing gas") can be converted into azo dyes by reaction with arenes in the presence of AlCl or HCl. The azo coupling can be achieved with electron-rich aromatic compounds such as mesitylene, trimethoxybenzene, azulene, or dibenzo-18-crown-6. The latter coupling reaction allows for the easy preparation of a colorimetric sensor for potassium or sodium ions. As a putative intermediate of the reaction with acid, we were able to isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Over the last decade, MICs have been used extensively as ligands for transition and main group metal complexes [3–10] . Furthermore, MICs were employed for small molecule activation, [3–10,13–17] and as metal‐free catalysts for polymerization reactions [3–10,18–20] . The electronic properties of mesoionic imidazolylidenes have been examined experimentally [21–27] and theoretically [28–31] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, MICs have been used extensively as ligands for transition and main group metal complexes [3–10] . Furthermore, MICs were employed for small molecule activation, [3–10,13–17] and as metal‐free catalysts for polymerization reactions [3–10,18–20] . The electronic properties of mesoionic imidazolylidenes have been examined experimentally [21–27] and theoretically [28–31] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] Over the last decade, MICs have been used extensively as ligands for transition and main group metal complexes. [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ] Furthermore, MICs were employed for small molecule activation,[ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 13 , 14 , 15 , 16 , 17 ] and as metal‐free catalysts for polymerization reactions. [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 18 , 19 , 20 ] The electronic properties of mesoionic imidazolylidenes have been examined experimentally[ 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…A condensation reaction with remaining NHO then provides the dimers 1-3. Presumably, the condensation reaction is initiated by N-O bond rupture of the diazohydroxide B, 12 forming either a vinyl diazonium compound or a diazoalkene. 13 Scheme 2.…”
mentioning
confidence: 99%
“…Analysis of 1 and 3 by single-crystal X-ray crystallography showed that azo-bridged NHO dimers had formed (for details, see the Supporting Information (SI)). The formation of these dimers can be rationalized by assuming that the reactions proceed via zwitterionic NHO–N 2 O adducts of type A (Scheme ), which can tautomerize to the diazohydroxides B . A condensation reaction with remaining NHO then provides the dimers 1 – 3 .…”
mentioning
confidence: 99%
“…Our results suggest that activation of N 2 O by strong Lewis acids holds promise in exploring its utility as an oxidant. Activation by Lewis acids is a much less studied area compared to the nucleophilic activation/fixation of N 2 O,,, and at the same time bears relevance to the enzymatic reduction of N 2 O …”
Section: Discussionmentioning
confidence: 99%